2017
DOI: 10.1038/srep41025
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance and biometric measurements show that a savanna ecosystem in Southwest China is a carbon sink

Abstract: Savanna ecosystems play a crucial role in the global carbon cycle. However, there is a gap in our understanding of carbon fluxes in the savanna ecosystems of Southeast Asia. In this study, the eddy covariance technique (EC) and the biometric-based method (BM) were used to determine carbon exchange in a savanna ecosystem in Southwest China. The BM-based net ecosystem production (NEP) was 0.96 tC ha −1 yr −1 . The EC-based estimates of the average annual gross primary productivity (GPP), ecosystem respiration (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 81 publications
1
25
0
Order By: Relevance
“…Forests are primary carbon absorbers, and the carbon sequestration function of plantation forests can help mitigate global climate change [68,69]. Some scholars have also come to a similar conclusion; that is, an important factor in the change of carbon sequestration eco-services is that the government reduces ecological land area to increase construction land area [70][71][72]. Our results also verify the conclusions of these scholars.…”
Section: Discussionsupporting
confidence: 79%
“…Forests are primary carbon absorbers, and the carbon sequestration function of plantation forests can help mitigate global climate change [68,69]. Some scholars have also come to a similar conclusion; that is, an important factor in the change of carbon sequestration eco-services is that the government reduces ecological land area to increase construction land area [70][71][72]. Our results also verify the conclusions of these scholars.…”
Section: Discussionsupporting
confidence: 79%
“…However, some other studies showed that drought could increase the soil respiration, and weaken the strength of ecosystems carbon sink and even change them into carbon sources (Cox et al 2000;Jones et al 2003;Ciais et al 2005;Shi et al 2014), but these findings are often uncertain (Sowerby et al 2008;Zhang et al 2015). By both eddy covariance and biometric methods, Fei et al (2017) found that the Yuanjiang savanna ecosystem was a weak carbon sink. Strong seasonal variation of NEE was observed at the study site, and the annual NEE varied with annual precipitation year by year.…”
Section: Effects Of Precipitation Reduction Treatments On Ecosystem Cmentioning
confidence: 98%
“…, Fei et al. ), thus representing a significant portion of the global carbon cycle (Bombelli et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding savanna structure and function is critically important, as savannas cover~15% of the global land surface (Ma et al 2013) and con-tribute~30% to global net primary production (NPP, Field et al 1998, Fei et al 2017, thus representing a significant portion of the global carbon cycle (Bombelli et al 2009). Nevertheless, savanna ecosystems vary across the globe based on their underlying geology and regional climates (Bond et al 2003, Vaughn et al 2015.…”
Section: Introductionmentioning
confidence: 99%